How to win the basketball Euroleague? Game performance determining sports results during 2003-2016 matches - Mikolajec, K.; Banys, D.; Zurowska-Cegielska, J.; Zawartka, M.; Gryko, K. (Journal of Human Kinetics, 2021)
The main aim of this study was to establish game-related statistics that determined sport results in the Basketball EuroLeague between 2003 and 2016. The study encompasses matches played by 10 teams during 13 consecutive seasons of the EuroLeague. Twenty-two offensive and defensive game related variables were registered. Calculations were performed to establish which of the variables determined performance in the Basketball EuroLeague matches within the analysed period. Based on a number of mathematical and statistical analyses, the elements of play that had the highest effect on sports success were selected. The following determinants displayed the most significant correlations with sport results in the EuroLeague within the analysed period: two-point shots made (2PT-made), twopoint shot attempts (2PT-attempts), three-point shots made (3PT-made), one-point shots made (1PT-made), one-point shot attempts (1PT-attempts), assists, fouls and field goals made. The game outcome in basketball is influenced by many variables which may not always be significant in a given match. However, the continuous effort to maintain these variables at the highest possible level is advantageous over less-organised teams.